Measuring First Year Student Scientific Literacy Skills using Test of Scientific Literacy Skills (TOSLS) - Chandra Adi Prabowo; Hasminar Rachman Fidiastuti (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2017)
The purpose of thisstudy was to determine the scientific literacy skills of first year student of biology education study program in Universitas Tribhuwana Tunggadewi. Subjects of this studyare50 students of biology education study program at academic year 2017/2018. Subjects of the study are a first year student when data collection conducted. Student scientific literacy skills was measured using test of scientific literacy skills (TOSLS) that consist of 28 test item to measuring two aspect of student scientific literacy skills. Collected data analyzed by descriptive quantitative methods to get a general information about student scientific literacy skills according to quantitative data. The result of the studyare the scientific literacy skills of first year student of biology education program generally classified in a low level. According to the result of the study, learning reorientation needed to enhancing students scientific literacy skills.